Forward Position Solution and Singularity Analysis of a 3SPS+1PS Bionic Parallel Manipulator - Li Yang; Cheng Gang; Feng Lanlan (Jixie chuandong)
In order to overcome the defects of traditional serial hip joint testing machine on high speed,complex motion simulation and large dynamic loading,aparallel hip joint testing machine with a3SPS+1PS spatial parallel manipulator as the core module is developed.The complicated forward position solution and the singularity are significant difficulties of its application.An analytical model of forward position analysis is built with the coordinates of hinge points on the moving platform and a univariate polynomial equation of higher degree is obtained,proving that there exist 8forward solution for a single input at most.The singular status of the testing machine under required motions is investigated according to the Jacobian matrix.The two singular points are proved to be the forward singularities caused by the overlaps of the forward position solution.Then the corresponding avoidance strategy is given.